Treatment in certified cancer centers is related to better survival in patients with colon and rectal cancer: evidence from a large German cohort study - Bierbaum, Veronika; Bobeth, Christoph; Roessler, Martin; Gerken, Michael; Tol, Kees Kleihues-van; Reißfelder, Christoph; Fürst, Alois; Günster, Christian; Dröge, Patrik; Ruhnke, Thomas; Klinkhammer-Schalke, Monika; Schmitt, Jochen; et al. (World journal of surgical oncology, 2024)
Background: Certified cancer centers aim to ensure high-quality care by establishing structural and procedural standards according to evidence-based guidelines. Despite the high clinical and health policy relevance, evidence from a nation-wide study for the effectiveness of care for colorectal cancer in certified centers vs. other hospitals in Germany is still missing. Methods: In a retrospective cohort study covering the years 2009–2017, we analyzed patient data using demographic information, diagnoses, and treatments from a nationwide statutory health insurance enriched with information on certification. We investigated whether patients with incident colon or rectal cancer did benefit from primary therapy in a certified cancer center. We used relative survival analysis taking into account mortality data of the German population and adjustment for patient and hospital characteristics via Cox regression with shared frailty for patients in hospitals with and without certification. Results: The cohorts for colon and rectal cancer consisted of 109,518 and 51,417 patients, respectively, treated in a total of 1052 hospitals. 37.2% of patients with colon and 42.9% of patients with rectal cancer were treated in a certified center. Patient age, sex, comorbidities, secondary malignoma, and distant metastases were similar across groups (certified/non-certified) for both colon and rectal cancer. Relative survival analysis showed significantly better survival of patients treated in a certified center, with 68.3% (non-certified hospitals 65.8%) 5-year survival for treatment of colon cancer in certified (p < 0.001) and 65.0% (58.8%) 5-year survival in case of rectal cancer (p < 0.001), respectively. Cox regression with adjustment for relevant covariates yielded a lower hazard of death for patients treated in certified centers for both colon (HR = 0.92, 95% CI = 0.89–0.95) and rectal cancer (HR = 0.92, 95% CI = 0.88–0.95). The results remained robust in a series of sensitivity analyses. Conclusions: This large cohort study yields new important evidence that patients with colorectal cancer have a better chance of survival if treated in a certified cancer center. Certification thus provides one powerful means to improve the quality of care for colorectal cancer. To decrease the burden of disease, more patients should thus receive cancer care in a certified center.
Gesehen am 04.04.2024